Peningkatan Kapasitas Kelembagaan Partai Politik untuk Mewujudkan Tindakan Afirmatif di Kalimantan Selatan - Ellisa Vikalista; Hardi Warsono; Rina Martini; Dewi Erowati (Jurnal HAM, 2023)
Affirmative action is a program that promotes equal and equitable representation for the involvement and inclusion of women in politics and governance, based on the recognition that women's rights are part of broader human rights. This study's objective is to thoroughly examine the practical use of affirmative action in national and regional political spheres, with a particular emphasis on Southern Kalimantan, which exhibits both patriarchal cultural idiosyncrasies and societal openness. Moreover, the study examines whether providing focused political education to female cadres within the established political party structure can increase women's representation. This study selects samples from five branches of the DPD/DPW of prominent political parties identified as the top five vote-getters in the 2019 elections in South Kalimantan. The use of institutional theory is encompassed within the analytical approach. Utilizing a descriptive qualitative methodology, the process of selecting study participants involves purposive sampling, which includes primary and secondary data sources. The results of this study significantly contribute to the support and validation of affirmative action policies and improve access to women's representation by emphasizing the importance of institutional aspects inside political parties. Promoting political education for women cadres directly fulfills fundamental elements of women's political and human rights. This effort requires the courage and generosity of political parties to advocate for special political education to be included in the party's constitution as a formal legal basis and a long-term commitment to upholding affirmative action as a social obligation of political parties.